Making Sense of the Unique Pain of Survivors: A Psychoeducational Approach for Suicide Bereavement - Berardelli, Isabella; Erbuto, Denise; Rogante, Elena; Sarubbi, Salvatore; Lester, David; Pompili, Maurizio (Frontiers in Psychology, 2020)
Grief, guilt, abandonment, anger, shame, and rejection are the most common feelings experienced by suicide survivors, who differ from other bereaved individuals for the intensity of these feelings. Moreover, suicide risk and psychiatric disorders associated with suicidality are more frequent in people who have lost a loved person by suicide. Given the complexity and the consequences linked to the suicide of a loved person it is nevessary to act promptly. Among the various strategies, psychoeducation has proved effective for several mental disorders and for suicide bereavement. It is a therapeutic intervention aimed to identify and understand the psychological features associated with the mental pain of suicide survivors, with the aim of facilitating the management of the illness and the recognition of relationships in the social environment. We developed a psychoeducational group that took place at the Suicide Prevention Center of the Sant’Andrea Hospital in Rome. It was a homogeneous, finite-group composed of 8-12 suicide survivors and conducted by two trained psychologists supervised weekly by the Director of the Suicide Prevention Center. The intervention comprised 21 weekly sessions of 90 minutes. Each session concerned a determined topic and began with the presentation of the issue, continued with specific exercises, and finished with a group discussion. The main goals of the group were to provide support, normalize the reactions of the survivors, assist them in reducing their emotional suffering and their feelings about suicide, investigate the potential presence of suicide risk, implement prevention strategies, and integrate the loss of the loved person.The psychoeducational approach we delivered for suicide survivors allows individuals to interact with other individuals in the same situation in order to help them resume the normal course of life, placing the suicide of a loved person in a broader perspective.